2017
DOI: 10.3389/fphar.2017.00700
|View full text |Cite
|
Sign up to set email alerts
|

Antiparkinsonian Efficacy of Guanosine in Rodent Models of Movement Disorder

Abstract: Guanosine (GUO) is a guanine-based purine nucleoside with important trophic functions and promising neuroprotective properties. Although the neuroprotective effects of GUO have been corroborated in cellular models of Parkinson’s disease (PD), its efficacy as an antiparkinsonian agent has not been fully explored in PD animal models. Accordingly, we evaluated the effectiveness of GUO in reversing motor impairments in several rodent movement disorder models, including catalepsy, tremor, and hemiparkinsonism. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…In addition, guanosine potentiated contralateral rotations induced by L-DOPA in unilaterally 6-hydroxydopamine (6-OHDA)-injured rats and displayed antidyskinetic efficacy in the L-DOPA-induced dyskinesia (LID) animal model. These results support the potential usefulness of guanosine in PD management, including its capacity to reduce dyskinesia when used in combination with L-DOPA (Massari et al, 2017 ).…”
Section: Neurotrophic and Neuroprotective Effects Of Gbpssupporting
confidence: 77%
“…In addition, guanosine potentiated contralateral rotations induced by L-DOPA in unilaterally 6-hydroxydopamine (6-OHDA)-injured rats and displayed antidyskinetic efficacy in the L-DOPA-induced dyskinesia (LID) animal model. These results support the potential usefulness of guanosine in PD management, including its capacity to reduce dyskinesia when used in combination with L-DOPA (Massari et al, 2017 ).…”
Section: Neurotrophic and Neuroprotective Effects Of Gbpssupporting
confidence: 77%
“…However, induction of oxidative stress, increased formation of the proinflammatory cytokines, mitochondrial dysfunction and induction of apoptosis are suggested as precipitating factorsfor PD[26].In the present study, 6-OHDA injection induced significant decrease in the striatal dopamine and total swim score associated with significant increase in the catalepsy score compared to the control group. This was in the same line with Beppe et al[27] and Massari et al[28] who reported that 6-OHDA induces loss of the dopaminergic neurons in the substantia nigra leading to decreased striatal dopamine. Zeng et al[5] suggested that the alteration of the behavioral tests induced by 6-OHDA can be attributed to disruption of the balance between the glutamatergic and GABAergic activities in the brain.…”
supporting
confidence: 89%
“…and/or VU0255035 (10 mg/kg, i.p.) was administered, and 1.5 h later, catalepsy was measured as described previously (Massari et al, 2017;Taura et al, 2017). Briefly, using a stopwatch with a cutoff time of 120 s, the duration of an abnormal upright posture was measured, in which the forepaws of the mouse were placed on a horizontal wooden bar (0.6-cm diameter) that was located 4.5 cm above the floor.…”
Section: Horizontal Bar Testmentioning
confidence: 99%
“…was administered 1.5 h before the test and 22 ± 2 h after reserpine treatment. The tremulous jaw movements (TJMs) were measured with handoperated counters, as described previously (Massari et al, 2017). Briefly, the mice were placed individually in a glass cylinder (13-cm diameter) and allowed to habituate for 10 min.…”
Section: Tremulous Jaw Movementsmentioning
confidence: 99%